Messages from Ukraine - Bucken-Knapp, Gregg (University of Toronto Press, 2022)
On February 24, 2022, Russia launched a full-scale invasion of Ukraine that dominated headlines around the world. Millions of Ukrainians would flee the country, and a third of the population would be displaced. In the days following the invasion, Swedish migration expert Gregg Bucken-Knapp sent text messages to his Ukrainian colleagues, offering support and assistance. These were their responses. In a series of graphic vignettes, Messages from Ukraine takes the words of Ukrainian migration professionals and transforms them into snapshots of how war affects the lives of everyday people: those who are forced to flee home and seek safety elsewhere, those who choose to stay and volunteer or fight, those who witness events unfolding from afar, and those who find themselves trapped in cities under siege. Messages from Ukraine captures a moment in time to tell a timeless story about war, displacement, determination, and resilience. Proceeds from the sale of Messages from Ukraine will go to the Canada-Ukraine Foundation, a national charitable foundation that provides humanitarian aid to the people of Ukraine.